Synthesis and Characterization of Salamo-Type Bisoxime Compounds Based on 2-Hydroxy-4-methoxybenzaldehyde and Bis(aminooxy)alkane - Wang, Li; Zhou, Wei-Min; Li, Gang; Zhang, Yang (Asian Journal of Chemistry, 2014)
Three new Salamo-type bisoxime compounds H2L1-H2L3 have been synthesized from 2-hydroxy-4-methoxybenzaldehyde and 1,5-bis(aminooxy)pentane, 1,6-bis(aminooxy)hexane or 1,9-bis(aminooxy)nonane in hot ethanol medium, respectively and characterized by elemental analysis, IR and 1H NMR spectroscopy.